218 Delaware Building: Adaptive Re-use in the Historic River Quay - John Jesik; Matt Kovatovich; Allan Mellske (Oz, 1987)
Beginning with the industrial revolution, buildings housing light industrial functions were a vital part of the urban fabric. Usually clustered just outside of business centers in the city environs, the buildings were vacated as companies outgrew them, moving to industrial parks in suburban locations.